Six propositions against ageism in the COVID-19 pandemic - Ehni, Hans-Jörg; Wahl, Hans-Werner (Journal of aging & social policy, 2020)
The risk of developing severe illness from COVID-19 and of dying from it increases with age. This statistical association has led to numerous highly problematic policy suggestions and comments revealing underlying ageist attitudes and promoting age discrimination. Such attitudes are based on negative stereotypes on the health and functioning of older adults. As a result, the lives of older people are disvalued, including in possible triage situations and in the potential limitation of some measures against the spread of the pandemic to older adults. These outcomes are unjustified and unethical. We develop six propositions against the ageism underlying these suggestions to spur a more adequate response to the current pandemic in which the needs and dignity of older people are respected.
Gesehen am 29.07.2020